1998
DOI: 10.1080/02705060.1998.9663638
|View full text |Cite
|
Sign up to set email alerts
|

Movement Patterns of the White-clawed Crayfish,Austropotamobius pallipes, in a Tuscan Stream

Abstract: We analyzed spatial behavior in the white-clawed crayfish, Austropotamobius pallipes, inhabiting a stream in Tuscany (Italy). Our study suggests an overall complex movement pattern , where nomadic movements are intercalated by stationary phases. There was a low rate of recapture within the stretch of stream inspected, suggesting either a tendency of the species to disperse or a mortality rate caused by predators or the loss of tags with molts. However, one part of the population showed a conservative use of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 18 publications
(29 reference statements)
4
40
1
2
Order By: Relevance
“…In general, there was no clear preference for upstream or downstream movements of A. torrentium in the Biberbach, Lower Austria. Comparable results are published for populations of A. pallipes by GHERARDI, BARBARESI and VILANELLI, 1998, and ROBINSON, THOM and LUCAS, 2000. KLOSTERMAN and GOLDMAN, 1981, showed that juveniles of signal crayfish, Pacifastacus leniusculus, had a clear preference for upstream movements in the laboratory.…”
Section: Figuresupporting
confidence: 65%
“…In general, there was no clear preference for upstream or downstream movements of A. torrentium in the Biberbach, Lower Austria. Comparable results are published for populations of A. pallipes by GHERARDI, BARBARESI and VILANELLI, 1998, and ROBINSON, THOM and LUCAS, 2000. KLOSTERMAN and GOLDMAN, 1981, showed that juveniles of signal crayfish, Pacifastacus leniusculus, had a clear preference for upstream movements in the laboratory.…”
Section: Figuresupporting
confidence: 65%
“…There have been suggestions that the composition of diet and feeding behaviour of crayfish varies with season (Goddard, 1988;Guan and Wiles, 1998), although evidence remains limited. Crayfish activity is seasonally variable being strongly regulated by water temperature (Gheradi et al, 1998;Bubb et al, 2004) as is the availability of macroinvertebrate prey (Allan, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Köksal (1988) reported that the males of A. leptodactylus were more active than the females, and also females were inactive during the breeding season (November to June) and the proportion of females per catch ranged from 29-43% from November to the end of June. The lower catches during winter and spring with respect to summer and autumn could be related to minor activity of crayfish after breeding and later, for females only, after spawning (Gherardi et al, 1997;Kirjavainen and Westman, 1999;Grandjean et al, 2000;Capurro et al, 2007). Differences in sex ratios over seasons could mainly be due to differences in the activity pattern of males and females (Westin and Gydemo, 1989;Hudina et al, 2008).…”
Section: Discussionmentioning
confidence: 99%